Pengaruh Kepemimpinan Transformasional , Pelatihan , dan Pengembangan Karir terhadap Kinerja Karyawan pada PTPN IV (Persero) Unit Tanah Itam Ulu Kabupaten Batu Bara - Rizky Septio; Hadi Suriono (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance remains a key issue in plantation companies, particularly in relation to leadership practices, training effectiveness, and career development systems that are not yet fully optimized. This study aims to examine the partial and simultaneous effects of transformational leadership, training, and career development on employee performance at PTPN IV (Persero) Unit Tanah Itam Ulu. A quantitative approach with a causal design was applied, involving 62 employees selected through simple random sampling. Data were collected using questionnaires and analyzed using multiple linear regression supported by classical assumption tests. The results indicate that transformational leadership, training, and career development each have a positive and significant effect on employee performance. Simultaneously, these variables also show a significant combined influence, with an adjusted R Square value of 0.403, indicating that 40.3% of performance variation can be explained by the model. Among the variables, training demonstrates the most dominant contribution. These findings highlight the importance of strengthening leadership quality, improving training implementation, and providing clearer career development pathways to enhance employee performance.